Atypical presentation of ruptured aneurysmal right sinus of Valsalva with severe aortic insufficiency - Serrano-Sánchez, Miguel Ángel (2023)
Aneurysm of the Sinus of Valsalva (ASV) is a rare abnormality and affects less than 0.1% of the general population. We describe the case of a 37-year-old woman with a clinical presentation characterized by dyspnea, palpitations, and syncope of 6 years of evolution. The echocardiographic study revealed a right ASV with a sub pulmonary interventricular perforation of 8mm and producing a regurgitant jet into the right ventricle, causing dilatation of the right ventricular outflow tract, pulmonary artery, and severe aortic insufficiency Carpentier ID. The patient underwent successful repair of the defect and interventricular perforation, and valve replacement was not necessary. Timely echocardiographic diagnosis and early surgery are the main predictors that make the difference between an excellent outcome and certain death.